ANALYSIS OF THE LENDING PRACTICE OF THE REAL SECTOR OF THE ECONOMY BY COMMERCIAL BANKS - Zokirova Feruza Farkhod kizi (Scholar Express Journals, 2023)
In the article Analysis of the practice of lending to the real sector of the economy by commercial banks the opinions of the world's leading scientists were studied, the situation of the banking sector of Uzbekistan at the beginning of 2017-2022 was analyzed, the forms and main directions and trends of financial support of the real sector of Uzbekistan were mentioned, the development of practice of lending to the real sector of the economy by commercial banks of Uzbekistan based conclusions and proposals were developed and recommendations for application in our country were made.
Keywords: investment; commercial bank; private sector